Effectiveness and safety of bleaching agents on lithium disilicate glass ceramics - Alper Ozdogan; Nihan Kaya (Tabriz University of Medical Sciences, 2022)
Background. Aesthetic expectations have increased the use of aesthetic materials in dentistry. Lithium disilicates are frequently used materials for these expectations. Bleaching is another method used to provide aesthetics. Bleaching processes on restorative materials are not fully known. This study investigated the effect of at-home and in-office bleaching methods on the color change, surface roughness, and topography of lithium disilicate glass-ceramic materials produced with two different techniques and subjected to different polishing procedures. Methods. A total of 144 disc-shaped pressed and computer-aided design (CAD) lithium disilicate glass-ceramic specimens were randomly divided into four groups. Glazing and three different chair-side polishing procedures were performed. The specimens in each group were randomly divided into two groups and subjected to at-home and in-office bleaching processes (n=9). The home bleaching process was repeated with 16% carbamide peroxide agent for six hours for seven days, while the in-office bleaching process was applied with 40% hydrogen peroxide agent for two sessions of 20 minutes. After the bleaching processes, the final color and surface roughness experiments of the specimens were carried out, and the results were recorded. ANOVA and Tukey multiple comparison tests were used FOR the statistical analysis of the data (α=0.05). Results. The material*polish*bleaching, polish*bleaching, material*bleaching, and material*polishing interactions were not statistically significant regarding color and roughness changes of both specimens (P>0.05). Conclusion. Both bleaching processes can be safely applied to lithium disilicate glass-ceramic materials.